2003
DOI: 10.1128/jcm.41.5.2203-2205.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Candida albicans Oral Strains from Healthy Individuals by Polymorphic Microsatellite Locus Analysis

Abstract: Analysis of a polymorphic microsatellite locus was applied to 85 Candida albicans strains from healthy individuals. Comparison with strains from nonhealthy individuals previously analyzed in our laboratory showed an overall similarity, suggesting that all commensal strains have the ability to develop as pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Bretagne et al observed a discriminatory power of 0.97 using a combination of the EF3, HIS3 and CDC3 microsatellites while Sampaio et al obtained a similar value using CAI alone. When combining the four microsatellites for typing a series of 174 unrelated strains of C. albicans, 23,28 we obtained a discriminatory power of 0.998, making this method even more suitable for epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bretagne et al observed a discriminatory power of 0.97 using a combination of the EF3, HIS3 and CDC3 microsatellites while Sampaio et al obtained a similar value using CAI alone. When combining the four microsatellites for typing a series of 174 unrelated strains of C. albicans, 23,28 we obtained a discriminatory power of 0.998, making this method even more suitable for epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Commensal isolates (group A) were collected from healthy individuals presenting as outpatients in a dental practice or at occupational medicine departments in Dijon and Chatillon sur Seine, two cities in Burgundy, in the northeast of France (details for the selection of these isolates are available in Dalle et al, 2003). Altogether, group A included 82 isolates from 82 distinct individuals.…”
Section: Albicans Isolatesmentioning
confidence: 99%
“…In this context, we previously addressed the question of the pathogenicity of lineages of C. albicans with regard to their genotype by determining the polymorphism of a unique microsatellite (CEF3) (Bretagne et al, 1997) in three series of C. albicans isolates: a series of commensal isolates collected in healthy individuals, a group of bloodstream isolates and a group of non-bloodstream clinical isolates (Dalle et al, 2003(Dalle et al, , 2000. Three major genotypes were identified in these studies that were overrepresented in both bloodstream, non-bloodstream and commensal isolates, suggesting that no correlation exists between C. albicans genotypes and its propensity for pathogenicity, at least as defined by the (CEF3) marker.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism for producing differences in allele sizes is primarily due to polymerase slippage errors (40). Microsatellites have successfully been used to type other pathogenic fungi, including Aspergillus fumigatus (3,27), Coccidioides immitis (19), Saccharomyces cerevisiae (21), and especially Candida albicans (6,13,14,18),…”
mentioning
confidence: 99%